Evaluation of platelet parameters, coagulation markers, antiphospholipid syndrome, and thyroid function in palestinian women with recurrent pregnancy loss - Ayman A. Najjar; Imam Hassouna; Mahmoud A. Srour; Hany M. Ibrahim; Randa Y. Assi; Heba M. Abd El Latif (BMC, 2023)
Abstract Background Multiple etiologies contribute to recurrent pregnancy loss (RPL) including immunological, endocrine, anatomical, genetic and infection but more than 50% of cases remain unexplained. Evidences of thrombotic and inflammatory processes were observed at maternal-fetal interface and considered pathological findings in most RPL cases including unexplained cases. This study aimed to evaluate the association between RPL and several risk factors: platelet parameters, coagulation factors, antiphospholipid syndrome, and thyroid function. Methods This is an unmatched case-control study that included 100 RPL and 100 control women. Anthropometric and health data were collected and a gynecologist examined participants to assure fitting the inclusion criteria. Platelet parameters [including Mean Platelet Mass (MPM), Concentration (MPC) and Volume (MPV)] and ratios (MPV/Platelet, MPC/Platelet, MPM/Platelet, Platelet/Mononuclear cells), coagulation markers [Protein C (PC), Protein S (PS), Antithrombin III, D-dimer], antiphospholipid antibodies [Anti-phospholipid (APA), Anti-cardiolipin (ACA) and anti-B2-glycoprotein 1], Lupus anticoagulant, Antinuclear antibodies, and thyroid function (Thyroid stimulating hormone and anti-thyroid peroxidase) were measured. Results Mean ages of cases and controls at marriage were 22.5 years for both, and their current ages were 29.4 and 33.0, respectively. 92% of cases and 99% of controls aged blow 30 years at marriage. 75% of cases have 3-4 miscarriages and 9% have ≥ 7 miscarriages. Our results indicated significantly lower male/female age ratio (p = .019), PC (p = .036) and PS (p = .025) in cases compared to controls. Plasma D-dimer (p = .020) and antiphospholipid antibodies [ACA (IgM and IgG), APA (IgM)] were significantly higher in cases compared to controls. No significant differences were observed between cases and controls concerning APA (IgG), anti-B2-glycoprotein 1 (IgM and IgG), Lupus anticoagulant, Antinuclear antibodies, platelet parameters, thyroid markers, family history of miscarriage, consanguineous marriage, and other health data. Conclusions This is the first study that investigated the association between platelet, coagulation, antiphospholipid, autoimmune and thyroid parameters, and RPL in Palestinian women. Significant associations between male/female age ratio, PC, PS, D-dimer, ACA (IgM, IgG), APA (IgM) and RPL were observed. These markers could be used in evaluating RPL. These findings confirm the heterogeneous nature of RPL and emphasize the need for further studies to find out risk factors for RPL.